GRAF AJAIB TOTAL - Riza Yani (Jurusan Matematika FMIPA Universitas Andalas Padang, 2013)
A total labeling of a graph with p vertices and q edges is dened as a one-to-one map taking the vertices and edges onto the integers 1; 2; ; p + q. Such a labelingis vertex magic if the sum of the label on a vertex and the labels on its incident edgesis a constant independent of the choice of vertex, and edge magic if the sum of an edgelabel and the labels of the endpoints of the edge is constant. In this paper we examinegraphs possessing a labeling that is simultaneously vertex magic and edge magic. Suchgraphs appear to be rare.